2003
DOI: 10.1016/s0006-3495(03)70031-9
|View full text |Cite
|
Sign up to set email alerts
|

MSI-78, an Analogue of the Magainin Antimicrobial Peptides, Disrupts Lipid Bilayer Structure via Positive Curvature Strain

Abstract: In this work, we present the first characterization of the cell lysing mechanism of MSI-78, an antimicrobial peptide. MSI-78 is an amphipathic alpha-helical peptide designed by Genaera Corporation as a synthetic analog to peptides from the magainin family. (31)P-NMR of mechanically aligned samples and differential scanning calorimetry (DSC) were used to study peptide-containing lipid bilayers. DSC showed that MSI-78 increased the fluid lamellar to inverted hexagonal phase transition temperature of 1,2-dipalmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
358
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 335 publications
(379 citation statements)
references
References 28 publications
20
358
0
1
Order By: Relevance
“…With the tilt of lipid molecules, the membrane also curves inside to form a hole lined by the lipid head groups and covered by peptides (Yeaman and Yount, 2003;Giuliani et al, 2007). The toroidalpore model is supported by recent studies, which confirmed that these pores are formed by peptides, such as maganins, mellitin and LL-37 (Hallock et al, 2003;Wildman et al, 2003). .…”
Section: Mechanism Of Actionmentioning
confidence: 81%
“…With the tilt of lipid molecules, the membrane also curves inside to form a hole lined by the lipid head groups and covered by peptides (Yeaman and Yount, 2003;Giuliani et al, 2007). The toroidalpore model is supported by recent studies, which confirmed that these pores are formed by peptides, such as maganins, mellitin and LL-37 (Hallock et al, 2003;Wildman et al, 2003). .…”
Section: Mechanism Of Actionmentioning
confidence: 81%
“…2D PISEMA experiments were performed on mechanically aligned lipid bilayers containing a 15 N labeled peptide as mentioned in our previous publication (40). A 50 kHz RF field was used in the 1 H channel at on-resonance during the preparation 90° pulse and CP, and a 35.355 kHz offset during the Lee-Goldburg (46) sequence in the SEMA (spin exchange at the magic angle) (39,40) sequence (or the t 1 period).…”
Section: Solid-state Nmrmentioning
confidence: 99%
“…All aligned 15 N chemical shift spectra were interpreted with reference to a powder pattern spectrum obtained from MLVs. A spectrum of MLVs containing 3 mole % SKP peptide labeled with 15 N-Leu-11 is given in Figure 6.…”
Section: Orientation Of Skp and Sa Peptides In Bilayersmentioning
confidence: 99%
See 2 more Smart Citations